The Determinants of Sources of Investment Financed by Local Government Units as Exemplified by Zamość Town - Klimczuk, Bogusław (Regional Barometer. Analyses & Prognoses, 2011)
To realize investment projects by local government units (LGUs) their financial sources are needed, as the example of these sources can be listed: budget earnings, the participation of inhabitants and private subjects in realization of public investment, budget surplus in previous years, target funds, foreign aid funds, credits, loans, leasing, community bonds. Among the most important internal factors which determine the source and the ways of investment financed by LGUs can be listed: 1) the size of LGUs measured by their area and number of inhabitants, 2) location and land development, 3) economic potential (eg. the number of economic subjects), 4) financial situation, rating assessment, audit assessment of the particular subject, 5) taken strategic position, 6) the level of innovation and pro-investment behaviour, 7) the style, methods and techniques of management, 8) employees' abilities and the competence of the management, 9) organizational culture, 10) experience in cooperation with financial institutions, business environment, non-governmental organizations and local society. Since 2004 Zamość Town with external support has realized investments which come to a total of 391 815 832,27 zlotys, worth mentioning is that 268 875 919,20 zlotys were paid by the UE, EEA, MF and state budget. Debts optimalization, the application of innovative financial sources of own contribution let Zamość town win next projects. Moreover, Zamość town constitutes a good example of diversification of investment of financial sources in LGUs.